High incidence of injuries at the Pyeongchang 2018 Paralympic Winter Games: a prospective cohort study of 6804 athlete days. Issue 1 (22nd February 2019) - Derman, Wayne; Runciman, Phoebe; Jordaan, Esme; Schwellnus, Martin; Blauwet, Cheri; Webborn, Nick; Lexell, Jan; van de Vliet, Peter; Kissick, James; Stomphorst, Jaap; Lee, Young-Hee; Kim, Keun-Suh
Abstract : Objective: To describe the epidemiology of sports injury at the Pyeongchang 2018 Paralympic Winter Games. Methods: 567 athletes from 49 countries were monitored daily for 12 days over the Pyeongchang 2018 Paralympic Winter Games (6804 athlete days). Injury data were obtained daily from teams with their own medical support (41 teams and 557 athletes) and teams without their own medical support (8 teams and 10 athletes) through two electronic data capturing systems. Results: 112 of 567 athletes (19.8%) reported a total of 142 injuries, with an injury incidence rate (IR) of 20.9 per 1000 athlete days (95% CI 17.4 to 25.0). The highest IR was reported for para snowboard (IR of 40.5 per 1000 athlete days [95% CI 28.5 to 57.5]; p<0.02), particularly in the lower limb and head/face/neck anatomical areas. Across all sports at the Games, acute traumatic injuries (IR of 16.2 per 1000 athlete days [95% CI 13.2 to 19.8]) and injuries to the shoulder/arm/elbow complex (IR of 5.7 per 1000 athlete days [95% CI 4.2 to 7.8]) were most common. However, most injuries (78.9%) did not require time loss. Conclusion: The new Paralympic Winter Games sport of Para snowboard requires attention to implement actions that will reduce injury risk. The shoulder was the most injured single joint—a consistent finding in elite para sport.